Prevention and control of COVID-19 in Primary Health Care: Recommendations for health professionals (Research, Society and Development, 2021)
Objective: To provide specific recommendations for infection control, prevention, and clinical management before COVID-19 for primary care health professionals. Methodology: This is a literature review searches were performed in the PubMed and Virtual Health Library (VHL) databases, using the combined descriptors based on the terms available in Health Sciences / Medical Subject Headings (DeCS / MeSH), search terms were: "Coronavirus infections"; "SARS-CoV-2"; "Infection control"; "Prevention and control"; " Unified Health System"; " Health Personnel "and" Family Health Strategy ". Searching for papers published between Jun/2020 and May/2021. The inclusion criterion was studied involving English and Portuguese languages, published in the period from 2020 to 2021, official documents from the Ministry of Health of Brazil and World Health Organization. Publications that did not present the objective similar to our study and duplicates were excluded.  Results: the main recommendations to be addressed to Primary Health Care professionals after reading and analyzing the selected material were: “Clinical management of flu syndrome in the (APS / ESF)”; "Identification of suspected case of influenza and covid-19 syndrome by professional category" and "The importance of Health Surveillance in the context of the pandemic". Conclusion: All members that make up the PHC health team have specific professional responsibilities and must be informed and attentive to safety recommendations to offer better assistance to users in SUS, as these guidelines are being updated amid the continuous spread of the pandemic in Brazil.